In-situ supercritical methanol transesterification for production of biodiesel from jatropha curcas l. seeds / Asnida Yanti Ani - Ani, Asnida Yanti (2010)
In-situ supercritical methanol transesterilication for production of biodiesel from Jairopha curcas L. (JCL) seeds was successfully carried out via 1000 ml hightemperature high-pressure hatch-wise reactor system in an absence of catalyst. In order to maximize the percent of crude biodiesel and FAMEs yield, four process variables were studied in this experiment, i.e. temperatures (180 to 300 °C). pressure (6 to 18 MPa), reaction time (5 to 35 mm) and seeds-to-methanol ratio(1 :15 to 1:45)using methanol as a solvent as well as reactant. Response Surface Methodology (RSM) was used to reduce the number of experimental runs required to generate sufficient information for a statistically acceptable results. In order to determine the best conditions of the variables in this in-situ process, Central Composite Rotatable Design (CCRD) was used for regression analysis and analysis of variance (ANOVA). Using RSM, the best conditions were chosen at temperature of 280.0 °C, pressure of 12.7 MPa, 30.0 min of reaction time and 1:40 (w/v) of seeds-to-methanol ratio. Interestingly, the qualitative Gas Chromatography (GC) analysis oil crude biodiescl showed the presence of FAMFs, indicating that the transesterification reaction had occurred during the in-situ process.